Математичні методи прогнозування забруднення повітря на основі нейронних мереж - Кит, М. О. (ХНУРЕ, 2021)
The work contains a solution of the problem of predicting air pollution by neural networks. Also, with assistance of Python programming language and Ju-pyter Notebook development environment, a software product was created and comparative analysis of corresponding methods and the received test result was carried out.
Keywords: прогнозування забруднення повітря; нейронна мережа; Long Short Term Memory; LSTM